Pengaruh Bauran Pemasaran Dan Kualitas Layanan Terhadap Keputusan Pembelian Di Calais Artisan Bubble Tea & Coffee Manokwari - Tifanny Lamria Sihole; Selmi Dedi; Louis S. Bopeng (JFRES Journal of Fiscal and Regional Economy Studies, 2020)
Purpose of this research is toidentify the influence between the variable for Marketing Mix (X1), and Service Quality (X2) affect in Purchase (Y) in Calais Artisan Bubble Tea & Coffee Manokwari. The accuration method whice use are purposive sampling method. The number of samples studied were 100 respondents who are consumers of Calais Artisan Bubble Tea & Coffee Manokwari. Based on the results of the study concluded that the multiple linear regresions equation for the effect of marketing mix and service quality on purchasing decisions Y=1,794+0,125X1+0,429X2. Marketing mix in fluence the purchasing decisions based on thitung (4,908) > ttabel (1,988). While simultaneously marketing mix and service quality significantly influence the purchasing decisions because the value of fhitung (98,154) > ftabel (3,09) and determinant coefficient (R Square) is 0,669.